IMPLEMENTASI KEBIJAKAN ANIES BASWEDAN-JRMK SEBAGAI JARINGAN INFORMAL TERHADAP PILKADA DKI JAKARTA 2017 - Rahmayanty, Kartikha Sri; Wahyuningroem, Sri Lestari (Universitas Jenderal Ahmad Yani, 2025)
In the effort to overcome poverty, Anies Baswedan took a strategic step by cooperating with JRMK as a political partner for the success of the 2017 DKI Jakarta elections. There are five points of agreement relating to urban planning and human rights. These points will be implemented if Anies is elected as Governor. As a political partner, JRMK uses this strategy to prevent evictions that often occur in Jakarta. The high level of poverty and slums due to urbanization in Jakarta makes evictions often occur. JRMK acts as an informal network, namely a network that is outside of power in coalition with the Government as a client. The results of the coalition also depend on the relationship in the communication pattern between the organization and the Government. The implementation of Anies' policy can be seen in the implementation of the Community Action Plan (CAP) in Akuarium and Tomang Villages. CAP is one of the steps to realize Jakarta Smart City and Green Building. In addition, the JakLingko transportation mode was also implemented to facilitate people's lives in forming people's awareness to use public transportation. The theory used in analyzing the research is an informal network. The research method used is an exploratory qualitative research method with literature study.